UX design with Figma user-centered interface design and prototyping with Figma - Green, Tom; Brandon, Kevin (Apress, 2024)
Maximize Figma's arsenal of tools and plugins within a team-based collaborative environment and accelerate your company's decision making. This book will show you where Figma fits into the user experience (UX) design process from documentation to developer handoff. Since its release as a browser-based design tool in 2016, Figma has fast become the de facto UX Design tool for the industry mainly due to its accessibility and ease of use. As you move through the book you will learn where Figma fits in the UX process. For example, using FigJam (an online whiteboard) for brainstorming, and creating interactive prototypes for mobile devices, tablets, and web sites. You'll also see how Figma is used to create and integrate with design systems, and how variables, when applied to design system components, can accelerate the design and development workflow. With the help of step-by-step examples, and using Figma's tools and templates, you'll create artifacts such as Flow and Journey diagrams, Personas, and wireframes. From there you will explore other design and interactivity features, and how to prepare a Figma file for handoff to a development team. This book is your roadmap to utilizing Figma, the industry's fastest growing collaborative design tool for building meaningful products. What You Will Learn Create interactive prototypes Test and submit designs for team review Understand the collaborative workflow involved in an UX project Prepare common UX documentation Who This Book Is For Designers, developers, and UX specialists with little-to-no Figma experience who are looking to integrate it within their workflows, and intermediate Figma users who are just starting to become involved in the collaborative UX workflow.
Includes index
Keywords: Computer-aided design -- Handbooks, manuals, etc; Computers -- Design; Computer graphics; Conception assistée par ordinateur; Guides, manuels, etc; Infographie; computer graphics